Something in the way they move: characteristics of identity present in faces, voices, body movements, and actions - Lander, Karen; Bennetts, Rachel (Frontiers in Psychology, 2025)
The recognition of familiar individuals relies not only on static features of the person but also on dynamic characteristics unique to each person’s movements. This mini review synthesizes current research on the role of motion in identity recognition, examining how characteristic dynamic cues from the face, voice, and body may contribute to perceivers’ ability to recognize familiar individuals. We highlight corresponding dynamic covariances that may be present across different aspects of an individual’s motion, such as those linking facial and vocal motion. We evaluate the extent to which dynamic patterns might form a coherent ‘dynamic fingerprint.’ Finally, we consider how variability, distinctiveness, and perceiver-related factors (e.g., individual differences and neural mechanisms) shape the recognition of identity through motion. We outline open questions and propose new directions for understanding the integration of dynamic information in person perception.